Lomami Buffer Zone (DRC): Forest composition, structure, and the sustainability of its use by local communities. (27th December 2021) - Batumike, Rodrigue; Imani, Gérard; Bisimwa, Benjamin; Mambo, Hwaba; Kalume, John; Kavuba, Fidele; Cuni‐Sanchez, Aida
Abstract: The recently created Lomami National Park has an extensive Buffer Zone where local communities are allowed to use forest products sustainably. However, the management of this Buffer Zone is hampered by inadequate understanding of the floristic composition and the impacts of harvesting certain plant products. To fill in this data gap, we established and sampled 30 vegetation plots of 40 × 40 m, and investigated the population structure of 11 useful tree species preferred by local communities. We found that the Buffer Zone is mostly composed of mixed‐species undisturbed old growth forest. It contains nine tree species of international conservation concern (listed in the IUCN Red list and/or apart from the Red list, Gibourtia demeusei, not been assessed by IUCN Red list, is listed in CITES Appendix II since January 2017; UNEP‐WCMC, Review of selected Dalbergia species and Guibourtia demeusei, UNEP‐WCMC, 2017). The floristic diversity of the Buffer Zone, which requires further investigation as some species remained unidentified. Most preferred tree species (including Garcinia kola and Milicia excelsa ) are abundant and showed a reverse‐J size distribution, indicating a relatively stable population structure. For these species, current levels of exploitation seem sustainable. Further research is needed for two nonabundant species of conservation concern ( Autranella congolensis and Michelsonia microphylla ). Although timber/firewood commercial harvesting is currently limited in the study area, the management plan of the Buffer Zone should consider these risks given increasing commercial hunting. Surveys and permanent plots provide essential information to guide the management of newly formed protected areas. Abstract in French is available with online material. Abstract : Lomami Buffer Zone hosts abundant mixed‐species undisturbed old growth forest. Nine tree species of international conservation concern are found in the Buffer Zone. Most preferred species are sustainably used: they are abundant and continuously recruiting. Résumé: Le parc national de Lomami récemment créé possède une vaste zone tampon où les communautés locales sont autorisées à utiliser les produits forestiers de manière durable. Cependant, la gestion de cette zone tampon est entravée par une mauvaise compréhension de la composition floristique et des impacts de la collecte de certains produits végétaux. Pour combler ce manque de données, on a établi 30 parcelles de végétation de 40 x 40 m et échantillonné les arbres de diamètre ≥10cm. On a étudié la structure de la population de onze espèces d'arbres utiles et préférées par les communautés locales. cette étude a démontré que la zone tampon est principalement composée de forêts anciennes non perturbées d'espèces mixtes. Dans cette zone, on a identifié neuf espèces d'arbres dont la conservation est préoccupante au niveau international (inscrites sur la liste rouge de l'UICN et/ou l'annexe CITES). La diversité floristique de la zone tampon nécessite une étude plus approfondie car certaines espèces sont restées non identifiées. La diversité floristique est vraisemblablement plus importante que la zone centrale, majoritairement formée de peuplements monodominants. Les espèces d'arbres préférées (y compris Garcinia kola et Milicia excelsa ) sont abondantes et présentent une distribution de taille en J inversé, indiquant une structure de population relativement stable. Pour ces espèces, les niveaux actuels d'exploitation semblent durables. Des recherches supplémentaires sont nécessaires pour deux espèces non abondantes dont la conservation est préoccupante ( Autranella congolensis et Michelsonia microphylla ). Bien que la collecte commerciale de bois d'œuvre/bois de chauffage soit actuellement limitée dans la zone d'étude, le plan de gestion de la zone tampon devrait tenir compte de ces risques compte tenu de l'augmentation de la chasse commerciale. Les placettes permanentes fournissent des informations essentielles pour guider la gestion des aires protégées nouvellement constituées.